Community Assistance in Understanding the Marriage Age Limit Law - Salma, Salma; Aisa, Siti; Awad, Nadila (Amalee: Indonesian Journal of Community Research and Engagement, 2024)
Changes in the minimum age for marriage regulated in Law Number 16 of 2019 have significantly impacted the number of applications for marriage dispensation in North Sulawesi. This service aims to carry out educational activities so that the public understands Law Number 16 of 2019 concerning Marriage Limits. Metode pengabdian ini menggunakan Participatory Rural Appraisal (PRA) atau pendekatan partisipatif, meliputi pelatihan, pendampingan, dan kolaborasi dengan pemangku kepentingan terkait. Implementasinya dimulai dari koordinasi, sosialisasi kegiatan, tahap pelaksanaan kegiatan, keberlanjutan program, penyusunan laporan, hingga monitoring dan evaluasi. The result of this service is that the socialization runs smoothly with a team that expands the target of this socialization to include teenagers, namely students and parents of teenage children. The efforts made by the service team are to provide an understanding of the impacts of underage marriage. This is very important to do considering the condition of society, where child marriages are increasing day by day.